2005
DOI: 10.1111/j.1439-0507.2004.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in Diyarbakır, Turkey

Abstract: The incidence and types of tinea capitis in 234 children aged 1-12 referred to our laboratory with a preliminary diagnosis of tinea capitis infection in the past 5 years were investigated. Tinea capitis was determined in 149 (63.7%) of these patients, of which agents grew in culture in 124 (83.2%). The most frequently isolated agents, in order of frequency, are as follows: Trichophyton violaceum (43.6%), Microsporum canis (37.9%), T. mentagrophytes (8.1%) and T. verrucosum (4.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…Because T. violaceum has been shown to be the most common cause of tinea capitis in a number of studies from West Asia and North Africa (1,5,16), while T. soudanense has been shown to be the most common cause of tinea capitis in a study of schoolchildren from the Ivory Coast (24), these organisms should be expected in children who have immigrated from these regions and have characteristic clinical findings. Since these species are rarely seen in the United States and usually fail to produce micro-or macroconidia, definitive identification may in some cases require molecular methods (20).…”
Section: Discussionmentioning
confidence: 99%
“…Because T. violaceum has been shown to be the most common cause of tinea capitis in a number of studies from West Asia and North Africa (1,5,16), while T. soudanense has been shown to be the most common cause of tinea capitis in a study of schoolchildren from the Ivory Coast (24), these organisms should be expected in children who have immigrated from these regions and have characteristic clinical findings. Since these species are rarely seen in the United States and usually fail to produce micro-or macroconidia, definitive identification may in some cases require molecular methods (20).…”
Section: Discussionmentioning
confidence: 99%
“…(2). In a study from Diyarbakır, Turkey, T. violaceum was detected in 43.6% of the cultures and M. canis in 37.9% of the cultures (8). The previous study from our center performed by Metin et al demonstrated that T. verrucosum was the most commonly isolated agent from cultures (9).…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies on the prevalence of TC and etiologic agents such as dermatophytes in Turkey, particularly in the East Anatolia region, which has a low socioeconomic level, poor hygienic conditions, and common cattle dealing (5,8). Metin et al performed a study on the prevalence of TC infection between 1997 and 1998 at our clinic (9).…”
Section: Introductionmentioning
confidence: 99%
“…Human infection results most often from direct contact with an infected animal, but may also be acquired indirectly through contact with a contaminated environment, 18 such as fungus-bearing hair and scales from infected animals. The prevalence of superficial mycoses caused by zoophilic dermatophytes was found to be significant in different parts of the world 24 especially in the tropical countries with warm and humid climate, crowded living and poor sanitary conditions. 25 Several studies have indicated that domestic animals (including cats, dogs, sheep, goats, pigs, rabbits, horses, donkeys, ducks and chickens) constitute important reservoir of human dermatophytic infections in Nigeria.…”
Section: Dermatophytosismentioning
confidence: 99%